Texaco - Chamoiseau, Patrick; Vinokurov, Val (New York Pantheon Books, 1997)
A novel of Martinique through the eyes of its people. Narrated by a black woman activist, the story spans 150 years, describing the end of slavery, the collapse of the sugar plantations, the coming of the oil companies and the new relations with France, of which the island is a department. By the author of Creole Folktales.
80476
Keywords: Women planners -- Fiction; Caribbean Area -- Fiction; Martinique -- Fiction; Historical fiction